Síntese, estrutura e atividade de peptídeos derivados de ParD, o antídoto do módulo toxina-antitoxina ParDE - Caires, Ana Carla [UNESP] (2014)
The ParE-ParD system represents a toxin-antitoxin module of the broad host range plasmid RK2. ParE (103 amino acids) is the toxin, whereas ParD (83 amino acids) constitutes the antidote able to neutralize ParE by forming a stable complex that is also effective in the autorepression of the parDE operon. The ParE toxin inhibits DNA gyrase activity and thereby blocks DNA replication. Several studies have shown that ParD consists of two structurally distinct regions: an N-terminal, orderly, consisting of the DNA binding site and another C-terminus, unstructured, where it is suggested to occur toxin binding. For binding with toxin, a current model of recognition and binding in TA systems invokes a disorder-to-order transition in the antitoxin. Specifically, a disordered region of the free antitoxin is organized into a well-defined secondary structure upon binding to its cognate toxin. But, no available data that proves the application of disorder-to-order transition model for ParE-ParD system. Therefore, this work aims to study the interaction of the ParE protein and its analogues with peptides from ParD antitoxin. Based on the structural information's of these proteins, peptide sequences derived from ParE and ParD were designed in order to find the minimal ParD structure able to neutralize the toxic effect of ParE. The peptide sequences were synthesized by solid phase methodology, purified and analyzed by HPLC and characterized by mass spectrometry. The interaction studies were performed by affinity chromatography and fluorescence quenching assays. The intrinsic fluorescence of the denominated ParEAC2 and ParEAC3 peptides was quenched by ParD derivatives, evidencing complex formation, results confirmed by affinity chromatography assays. Molecular Docking studies demonstrated that the interaction mode of ParEAC3-ParDAC3 complex was consistent with the obtained crystallographic complex ParE-ParD of...